Biological stable multifunctional cutting fluid and preparation method thereof
By combining vegetable oil-ethylene oxide-propylene oxide block copolymers with modified nanomaterials, the performance instability of cutting fluids under hard water conditions has been solved, resulting in a high-efficiency, environmentally friendly, multifunctional cutting fluid with excellent biological stability and lubricity, adaptability to different water qualities, and reduced production costs.
Patent Information
- Application Number
- CN202511879061.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-03-17
AI Technical Summary
Existing cutting fluids are insufficient in terms of biological stability, water quality adaptability, and multifunctionality. They are difficult to meet the requirements of long-term biological stability, broad-spectrum water quality adaptability, and multifunctionality at the same time. In particular, their performance is unstable under high-hardness water conditions, and they are difficult to balance lubrication and rust prevention performance.
By combining vegetable oil-ethylene oxide-propylene oxide block copolymers, modified nanomaterials, and composite bactericides, a highly efficient and stable lubrication-emulsification system is formed through precise control of surfactant ratios and component synergistic effects. This system enhances biological stability and water quality adaptability, and improves lubrication and rust prevention performance through the synergistic effect of nanomaterials.
It achieves excellent performance stability in both hard and soft water, significantly extends the service life of cutting fluid, reduces foam generation, improves lubricity and rust prevention, reduces production costs, and has good biodegradability and environmental performance.
Smart Images

Figure CN121674138A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metalworking lubrication technology, specifically relating to a bio-stable multifunctional cutting fluid and its preparation method. Background Technology
[0002] In metal processing, cutting fluid is a critical process fluid, and its performance directly affects machining efficiency, workpiece quality, tool life, and production costs. With increasingly stringent environmental regulations and higher user requirements for safe working environments, developing high-performance, long-life, and environmentally friendly cutting fluids has become an important research direction in the industry.
[0003] Existing cutting fluid technologies, especially emulsified and semi-synthetic cutting fluids, generally face two major challenges during long-term use: (1) Poor biological stability: They are easily corroded and deteriorated by microorganisms (such as bacteria and fungi), resulting in shortened service life, decreased lubrication performance, and odor, shortening the fluid replacement cycle, increasing treatment costs, and harming worker health and the workshop environment. (2) Weak water quality adaptability: They have poor adaptability to water quality (especially hard water with high calcium and magnesium ion content). When using high-hardness water to prepare the solution, the calcium and magnesium ions are prone to react with the anionic surfactants and soap components in the cutting fluid, leading to the destruction of solution stability and problems such as flocculation, demulsification, and soap precipitation, which seriously affect the performance. (3) Difficulty in balancing performance: It is difficult to balance rust prevention and lubrication performance, or multiple additives are required, resulting in complex formulations and possible antagonistic effects between components.
[0004] To address these challenges, researchers have made various attempts. For example, Chinese patent CN112300806A discloses a "long-lasting antibacterial semi-synthetic cutting fluid and its preparation method," which effectively improves the antibacterial properties of the cutting fluid by compounding a specific ratio of borate esters and isothiazolinone bactericides. However, this approach has limited improvement in adaptability to water hardness, and the bactericides used pose certain environmental and health risks. Chinese patent CN110591721B describes a "water-based cutting fluid suitable for hard water," which uses various nonionic surfactants and hard water dispersants to enhance its resistance to hard water, but its biological stability mainly relies on traditional preservatives, its long-lasting antibacterial ability is insufficient, and its function is relatively limited.
[0005] In summary, existing technologies often struggle to achieve an ideal balance between long-term biological stability, broad water quality adaptability, and multifunctionality (such as extreme pressure anti-wear, rust prevention, and cooling). Therefore, there is an urgent need in this field for a novel cutting fluid formulation and its preparation method that simultaneously possesses excellent biological stability to extend service life, broad adaptability to water of varying hardness to ensure stable performance, and integrates multiple functions such as lubrication, rust prevention, and cleaning to meet the demands of modern, efficient, and green manufacturing. Summary of the Invention
[0006] The purpose of this invention is to provide a bio-stable multifunctional cutting fluid and its preparation method, in order to solve the technical problems in the prior art.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: The technical solution provided by this invention is as follows: In a first aspect, the present invention provides a bio-stabilized multifunctional cutting fluid, wherein the bio-stabilized multifunctional cutting fluid comprises the following components by weight: Base oil 20-30%, vegetable oil, ethylene oxide, propylene oxide block copolymer 10-20%, lubricant 5-10%, extreme pressure anti-wear agent 2-5%, rust inhibitor 4-10%, antibacterial agent 0.3-2%, nano additives 0.6-1%, antioxidant 0.1-0.3%, triethanolamine 0.1-0.5%, balance water.
[0008] Preferably, the nano-additive is composed of polydopamine-modified MXene nanosheets and modified copper nanosheets in a mass ratio of 2:1.
[0009] Preferably, the preparation method of the vegetable oil ethylene oxide and propylene oxide block copolymer includes the following steps: A1: Add vegetable oil and catalyst to a dry, clean high-pressure reactor, heat and vacuum it while stirring to remove trace amounts of moisture from the raw materials; A2: Nitrogen gas is introduced into the reactor, then propylene oxide is added, and the temperature is raised to carry out the stirring reaction; A3: Add ethylene oxide to the reactor, react, and continue to maintain the temperature for 1 hour for aging; A4: Cool the reactants, add acetic acid to neutralize the catalyst, then dissolve the generated salt with water, allow the aqueous phase to stand and separate to obtain the crude product, and further dehydrate it under vacuum to obtain the vegetable oil ethylene oxide propylene oxide block copolymer.
[0010] Preferably, in step A1, the vegetable oil includes at least one of castor oil and chamomile oil; the heating temperature is 100-120℃, the vacuum dehydration time is 1-2h; and the catalyst is KOH.
[0011] Preferably, in step A1, the amount of catalyst used is 0.1-0.3% of the total mass of vegetable oil and propylene oxide.
[0012] Preferably, in step A2, the stirring reaction conditions are: stirring speed of 500-700 rpm, stirring reaction temperature of 115-130℃, and stirring reaction time of 4-6 h.
[0013] Preferably, in step A2, the mass ratio of vegetable oil to propylene oxide is 10:3-10.
[0014] Preferably, in step A3, the weight ratio of ethylene oxide (EO) to propylene oxide (PO) is 70-80:20-30; the reaction conditions are: reaction temperature of 115-130℃ and reaction time of 4-6h.
[0015] Preferably, in step A4, the mass ratio of acetic acid to KOH is 1.05-1.3:1; and the cooling temperature is 80-90℃.
[0016] Preferably, the lubricant is a compound of tetrameric castor oil ester and M28B tall oil in a mass ratio of 1-1.5:1.
[0017] Preferably, the extreme pressure anti-wear agent is a mixture of alkyl phosphate and aryl phosphate in a mass ratio of 1.5-2.5:1.
[0018] Through the above technical solution, the extreme pressure anti-wear agent is a compound of alkyl phosphate esters and aryl phosphate esters. The benzene ring in the aryl phosphate ester molecule has a large π bond, which can be easily and quickly physically adsorbed onto the metal surface through π-π stacking and van der Waals forces. It also possesses lone pairs of electrons, which can act as electron donors, forming a coordinate bond with the metal surface and creating a strong and dense adsorption film. Meanwhile, the POC bond of the alkyl phosphate ester breaks, releasing active phosphorus elements that react chemically with the metal (iron) to generate a low-shear-strength solid film of iron phosphate (FePO4) and its analogues. This reaction film is relatively soft and has a layered structure. When the metal surface is about to undergo welding under high pressure, this film preferentially undergoes shear slip, thus converting intense sliding friction into slip within the solid film, preventing tearing and welding of the metal itself. By adjusting the relative ratio of alkyl phosphate esters and aryl phosphate esters, synergistic effects are achieved, balancing lubrication and extreme pressure anti-wear properties, comprehensively improving the overall performance of the cutting fluid.
[0019] Preferably, the alkyl phosphate is LB400 phosphate; the aryl phosphate is 468 phosphate.
[0020] Preferably, the antibacterial agent is a complex of 1,3,5-tris(2-hydroxyethyl)-1,3,5-hexahydrotriazine and iodopropynyl butylcarbamate in a mass ratio of 1:1.
[0021] Preferably, the rust inhibitor is one or more of sebacic acid, naphthalic acid, tricarboxylic acid, tartaric acid, succinic acid, and isocitric acid.
[0022] Preferably, the base oil is rapeseed oil; the antioxidant is 4,4-methylene (2,6-di-tert-butylphenol).
[0023] Preferably, the method for preparing the polydopamine-modified MXene nanosheets includes the following steps: S1: LiF was added to an aqueous HCl solution, and Ti3AlC2 was slowly added. The mixture was stirred at a constant temperature to obtain multilayer MXene. After removing impurities, the mixture was freeze-dried to obtain MXene sheets. The MXene sheets were added to water and ultrasonically treated to obtain a 0.3wt% MXene nanosheet aqueous dispersion. S2: Dissolve dopamine hydrochloride in Tris-HCl solution and stir. Then add MXene nanosheet aqueous dispersion, continue stirring, wash, and freeze dry to obtain polydopamine-modified MXene nanosheets.
[0024] In the above process, MXene is obtained through HCl / LiF etching and layering. The dopamine-modified MXene surface usually carries a negative charge.
[0025] Preferably, in S1, the ratio of LiF, HCl, and Ti3AlC2 is 20-40g:300-600mL:20-40g; the concentration of the HCl aqueous solution is 9mol / L; the constant temperature stirring conditions are: constant temperature stirring temperature is 30-40℃, and constant temperature stirring time is 20-28h; the impurity removal method is: washing the multilayer MXene with water until pH is 7, centrifuging to collect the precipitate, redispersing the precipitate in 150-250mL of water, ultrasonically treating it at a power of 150-250W for 0.5-1.5h, and centrifuging it at a speed of 7000-9000rpm for 25-35min.
[0026] Preferably, in step S2, the ratio of dopamine hydrochloride, Tris-HCl solution, and MXene nanosheet aqueous dispersion is 0.6-1.2g:100-200mL:60-140mL; the pH of the Tris-HCl solution is 8.5; the stirring time is 25-35min; the mass fraction of the MXene nanosheet aqueous dispersion is 0.3wt%; the stirring time is continued for 20-28h; and the washing method involves washing the precipitate 3-5 times with ultrapure water and ethanol.
[0027] Preferably, the method for preparing the modified nano-copper includes the following steps: P1: Dissolve fatty alcohol polyoxyethylene ether in tetrahydrofuran, heat and add potassium hydroxide, stir and react, cool in an ice bath, add carbon disulfide and continue the reaction to remove the tetrahydrofuran solvent, and obtain fatty alcohol polyoxyethylene ether potassium xanthate. P2: Add potassium xanthate of fatty alcohol polyoxyethylene ether and copper nitrate to water, stir, add sodium borohydride to react, and centrifuge to obtain modified nano copper.
[0028] Preferably, in P1, the ratio of fatty alcohol polyoxyethylene ether, tetrahydrofuran, potassium hydroxide, and carbon disulfide is 10-20g:80-160mL:0.86-1.7g:1.18-2.4g; the heating temperature is 55-65℃; the stirring reaction time is 1.5-2.5h; and the reaction continues for 1.5-2.5h.
[0029] Preferably, in P2, the ratio of potassium xanthate, copper nitrate, water, and sodium borohydride is 6-12g:2.9-6g:100-200mL:0.45-0.9g; the stirring time is 1.5-2.5h; and the reaction time is 1.5-2.5h.
[0030] Secondly, the present invention also provides a method for preparing a bio-stabilized multifunctional cutting fluid, comprising the following steps: Step (1) Mix rapeseed oil, 90% of product A, lubricant, extreme pressure anti-wear agent, rust inhibitor, and 4,4-methylene (2,6-di-tert-butylphenol) according to the specified amount, heat to 50-60℃ and stir at 800-1200 rpm for 20-30 minutes to form an oil phase; Step (2) Dissolve the antibacterial agent in the remaining 10% of product A at 30-40℃, and add it to 70% of the total water at 50-55℃ to obtain an aqueous phase. Then, at 50-55℃, add the aqueous phase dropwise to the oil phase at a rate of 5-10 mL / min, while simultaneously shearing and emulsifying at 10,000-15,000 rpm for 25-35 min to obtain an emulsion. Step (3) Disperse polydopamine-modified MXene nanosheets and modified copper nanosheets with 5% of the total water volume using ultrasonic dispersion at 150-250W for 25-35 minutes. Then add them to the emulsion while stirring at 450-550 rpm. Then treat with high shear at 7000-9000 rpm for 8-12 minutes. Add the remaining 25% water and adjust the pH to 8.5-9.5 with 1 mol / L triethanolamine. Continue stirring for 25-35 minutes and let it stand at 45-50℃ for 1-2 hours to obtain a bio-stable multifunctional cutting fluid. Dilute it 5-10 times before use.
[0031] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention prepares a nonionic surfactant based on ethylene oxide-propylene oxide block copolymer made from vegetable oil. Its molecular design has the following multiple functions: (1) The lipophilic polyoxypropylene segments can be anchored in the oil phase, and the hydrophilic polyoxyethylene segments extend into the water phase, forming a dense and firm polymer adsorption layer at the oil-water interface, achieving efficient and stable emulsification through a strong steric hindrance effect. (2) This surfactant is nonionic and does not react with calcium and magnesium ions in water to form soap scum, thus maintaining excellent performance stability in both hard and soft water. (3) By precisely controlling the ratio and molecular weight of polyoxyethylene and polyoxypropylene segments, the copolymer exhibits controlled interfacial behavior in the system: it plays an excellent emulsifying role at the oil-water interface, while at the air-water interface, its molecules tend to penetrate the foam liquid film in a destructive manner (such as spreading displacement and bridging dehumidification effect), significantly reducing the generation and stability of foam, thereby effectively controlling the foam problem of cutting fluid. In addition, the copolymer has excellent wetting properties, which can help spread and adsorb other functional components on the metal surface.
[0032] 2. The addition of tetrameric castor oil ester and M28B tall oil to the bio-stable multifunctional cutting fluid prepared in this invention can effectively prevent direct contact between the tool and the workpiece, thereby significantly reducing tool wear, inhibiting built-up edge, and improving surface finish.
[0033] 3. This invention utilizes potassium xanthate from fatty alcohol polyoxyethylene ether to functionalize the surface of nano-copper, chemically anchoring the xanthate groups to the copper core, with its long chains forming a spatial barrier. Simultaneously, its sulfur-containing structure can react with the copper core in situ under thermal catalysis at the friction interface to generate a CuS / Cu2S extreme pressure lubricating film. This modified nano-copper, through its organic long chains, generates intermolecular forces such as hydrogen bonds with polydopamine-modified MXene nanosheets (rich in -OH and -NH functional groups), constructing a three-dimensional weakly cross-linked network structure in the fluid. This synergistically solves the sedimentation problem of nanomaterials (especially MXene sheets), endowing the cutting fluid with excellent long-term dispersion stability. During friction, the layered lubrication and high thermal conductivity of MXene synergistically work with the in-situ generated sulfide extreme pressure film of the nano-copper to achieve friction reduction, wear resistance, and temperature reduction. Furthermore, the modified nano-copper can also serve as a multifunctional additive to replace some lubricants and bactericides, significantly reducing the cost of cutting fluid production.
[0034] 4. The bactericide used in the bio-stable multifunctional cutting fluid prepared in this invention is a complex of iodopropynylhexylcarbamate and 1,3,5-tris(2-hydroxyethyl)-1,3,5-hexahydrotriazine. By adjusting the relative ratio of iodopropynylhexylcarbamate to 1,3,5-tris(2-hydroxyethyl)-1,3,5-hexahydrotriazine, comprehensive control of bacteria, fungi, and molds can be achieved, preventing the cutting fluid from becoming smelly and deteriorating, significantly extending the service life of the cutting fluid, and reducing the frequency of waste fluid treatment.
[0035] 5. The bio-stable multifunctional cutting fluid prepared in this invention uses a vegetable oil-based ethylene oxide-propylene oxide block copolymer to replace a larger amount of polyoxyethylene ether surfactant, resulting in higher biodegradability, lower foaming, and superior wetting, penetration, and emulsification capabilities, while also being more environmentally friendly. In this invention, when tetrameric castor oil oleate and M28B tall oil are compounded with the vegetable oil-based ethylene oxide-propylene oxide block copolymer surfactant, and nano-additives are added, a synergistic effect is achieved, further enhancing the overall performance of the cutting fluid. This compounding forms a highly efficient and stable lubrication-emulsification synergistic system, constructing a super-strong lubricating film in situ within the metalworking fluid, while simultaneously ensuring excellent emulsification stability, cooling properties, and biodegradability. Attached Figure Description
[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0037] Figure 1 This is a SEM image of the polydopamine-modified MXene nanosheets of the present invention; Figure 2 This is a line graph showing the lubricity of the bio-stabilized multifunctional cutting fluid of the present invention; Figure 3 This is a line graph illustrating the biostability of the bio-stable multifunctional cutting fluid of the present invention. Figure 4 This is a bar chart illustrating the biodegradability of the bio-stable multifunctional cutting fluid of the present invention. Detailed Implementation
[0038] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example
[0039] This embodiment discloses a method for preparing a vegetable oil ethylene oxide and propylene oxide block copolymer, comprising the following steps: A1: Add 100g castor oil and 0.4g KOH to a dry and clean high-pressure reactor, and dehydrate for 1.5h at 110℃ and a vacuum of -0.095MPa to remove trace amounts of moisture from the raw materials; A2: Nitrogen gas is introduced into the reactor of step (1) to replace the air in the reactor, and then the temperature is raised to 125°C. 34g of propylene oxide is slowly introduced and the pressure is kept at 0.3MPa. The reaction is carried out for 5 hours. A3: Slowly add 105g of ethylene oxide to the reactor, react at 125℃ for 5h, and then keep warm for 1h to ripen; A4: Cool the reactants to 85°C, add 0.6 mL of 80 wt% acetic acid to neutralize the catalyst, then add 80 mL of water to dissolve the generated salt, allow the aqueous phase to stand and separate to obtain the crude product, and further dehydrate it under vacuum to obtain the vegetable oil ethylene oxide propylene oxide block copolymer, which is called product A.
[0040] The initial foam volume of product A was 22 mL, and the foam volume was 10 mL after 5 min, with a critical surface tension of 33 mN / m. Example
[0041] Example 2 differs from Example 1 in that the amount of propylene oxide used in step A2 is 93.5g, and the amount of ethylene oxide used in step A3 is 218g, while other conditions remain unchanged, resulting in a vegetable oil ethylene oxide-propylene oxide block copolymer, referred to as product B.
[0042] The initial foam volume of product B is 25 mL, and the foam volume is 15 mL after 5 min. The critical surface tension is 28 mN / m. Example
[0043] Example 3 differs from Example 1 in that the amount of propylene oxide used in step A2 is 65g, and the amount of ethylene oxide used in step A3 is 200g, while other conditions remain unchanged, resulting in a vegetable oil ethylene oxide-propylene oxide block copolymer, referred to as product C.
[0044] The initial foam volume of product C is 15 mL, and the foam volume is 8 mL after 5 min, with a critical surface tension of 35 mN / m.
[0045] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the amount of propylene oxide used in step A2 is 150g, and the amount of ethylene oxide used in step A3 is 64g, while other conditions remain unchanged, resulting in a vegetable oil ethylene oxide-propylene oxide block copolymer, which is referred to as product D.
[0046] The initial foam volume of product D is 10 mL, and the foam volume is 3 mL after 5 min, with a critical surface tension of 42 mN / m.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the amount of propylene oxide used in step A2 is 56g, and the amount of ethylene oxide used in step A3 is 145g, while other conditions remain unchanged, resulting in a vegetable oil ethylene oxide-propylene oxide block copolymer, referred to as product E.
[0048] The initial foam volume of product E was 80 mL, and the foam volume was 32 mL after 5 min, with a critical surface tension of 38 mN / m. Example
[0049] This embodiment discloses a method for preparing polydopamine-modified MXene nanosheets, including the following steps: S1: Add 30g LiF to 450mL of 9mol / L HCl, then slowly add 30g Ti3AlC2, and stir at 35℃ for 24h to obtain multilayer MXene. Wash the multilayer MXene with water until pH 7, collect the precipitate by centrifugation, disperse the precipitate again in 200mL of water, sonicate at 200W for 1h, centrifuge at 8000rpm for 30min, freeze dry to obtain MXene sheets, add the MXene sheets to water and sonicate to obtain 0.3wt% MXene nanosheet aqueous dispersion; S2: Dissolve 0.9 g of dopamine hydrochloride in 150 mL of Tris-HCl solution with pH 8.5 and stir for 30 min to allow dopamine to self-polymerize in air to form polydopamine. Then add 100 mL of 0.3 wt% MXene nanosheet aqueous dispersion and continue stirring for 24 h. Wash the precipitate four times with ultrapure water and ethanol, and freeze-dry to obtain polydopamine-modified MXene nanosheets. Example
[0050] Example 5 differs from Example 4 in that: the amount of LiF used is 20g, the amount of Ti3AlC2 used is 40g, the amount of dopamine hydrochloride used is 0.6g, the amount of MXene nanosheet aqueous dispersion used is 140mL, and other conditions remain unchanged. Example
[0051] The difference between Example 6 and Example 4 is that the amount of LiF used is 40g, the amount of Ti3AlC2 used is 20g, the amount of dopamine hydrochloride used is 1.2g, the amount of MXene nanosheet aqueous dispersion used is 60mL, and other conditions remain unchanged. Example
[0052] This embodiment discloses a method for preparing modified nano-copper, including the following steps: P1: Dissolve 15g of fatty alcohol polyoxyethylene ether in 120mL of tetrahydrofuran, heat to 60℃, then add 1.2g of potassium hydroxide, stir and react for 2h, cool in an ice bath, add 1.8g of carbon disulfide, continue to react for 2h, remove the tetrahydrofuran solvent, and obtain fatty alcohol polyoxyethylene ether potassium xanthate. P2: Add 9g of fatty alcohol polyoxyethylene ether potassium xanthate and 4.5g of copper nitrate to 150mL of water, stir for 2h, add 0.7g of sodium borohydride, react for 2h, and then centrifuge to obtain modified nano copper. Example
[0053] The difference between Example 8 and Example 7 is that the amount of potassium xanthate of fatty alcohol polyoxyethylene ether is 12g, the amount of copper nitrate is 2.9g, and the amount of sodium borohydride is 0.9g, while all other conditions remain the same. Example
[0054] The difference between Example 9 and Example 7 is that the amount of potassium xanthate of fatty alcohol polyoxyethylene ether is 6g, the amount of copper nitrate is 6g, and the amount of sodium borohydride is 0.45g, while all other conditions remain the same. Example
[0055] This embodiment discloses a bio-stabilized multifunctional cutting fluid, which specifically comprises the following components by weight: 24g rapeseed oil, 15g product A prepared in Example 1, 8g lubricant, 3g extreme pressure anti-wear agent, 5.09g rust inhibitor, 1.1g antibacterial agent, 0.8g nano additive, 0.2g 4,4-methylene (2,6-di-tert-butylphenol), 42.8g water, and appropriate amount of triethanolamine.
[0056] Triethanolamine was added as a 1 mol / L aqueous solution during the preparation process to adjust the pH to 9; The lubricant is a compound of tetrameric ricinoleate and M28B tall oil in a mass ratio of 1.25:1; The extreme pressure anti-wear agent is a compound of LB400 phosphate ester and 468 phosphate ester in a mass ratio of 2:1; The rust inhibitor is a compound of tribasic acid, naphthalic acid, and benzotriazole in a mass ratio of 4:2:1. The antibacterial agent is a compound of 1,3,5-tris(2-hydroxyethyl)-1,3,5-hexahydrotriazine and iodopropynyl butylcarbamate in a mass ratio of 1:1. The nano-additive was prepared by compounding polydopamine-modified MXene nanosheets prepared in Example 4 and modified copper nanosheets prepared in Example 7 at a mass ratio of 2:1.
[0057] The preparation method of a bio-stabilized multifunctional cutting fluid includes the following steps: Step (1) Mix rapeseed oil, 90% of product A, lubricant, extreme pressure anti-wear agent, rust inhibitor, and 4,4-methylene (2,6-di-tert-butylphenol) according to the specified amount, heat to 65°C and stir at 1000 rpm for 25 minutes to form an oil phase; Step (2) Dissolve the antibacterial agent in the remaining 10% of product A at 35°C, and add it to 70% of the total water at 55°C to obtain an aqueous phase. Then, at 55°C, add the aqueous phase to the oil phase at a dropping rate of 7 mL / min, and simultaneously shear emulsify at a speed of 13000 rpm for 30 min to obtain an emulsion. Step (3) The polydopamine-modified MXene nanosheets and modified copper nanosheets were ultrasonically dispersed with 5% of the total water volume at a power of 200W for 30 minutes. Then, they were added to the emulsion while stirring at a speed of 500rpm. The mixture was then subjected to high shear treatment at a speed of 8000rpm for 10 minutes. The remaining 25% water was added, and the pH was adjusted to 9 with 1mol / L triethanolamine. The mixture was stirred for another 30 minutes and then allowed to stand at 46℃ for 1.5 hours to mature, thus obtaining a bio-stable multifunctional cutting fluid. Example
[0058] The cutting fluid and preparation method of Example 11 differ from those of Example 10 in that: product A prepared in Example 1 is replaced by an equal amount of product B prepared in Example 2, and the nano-additive is replaced by an equal amount of the nano-additive prepared by combining polydopamine-modified MXene nanosheets prepared in Example 5 and modified nano-copper prepared in Example 8 in a mass ratio of 2:1. All other conditions remain unchanged. Example
[0059] The cutting fluid and preparation method of Example 12 differ from those of Example 10 in that: product A prepared in Example 1 is replaced by an equal amount of product C prepared in Example 3, and the nano-additive is replaced by an equal amount of the nano-additive prepared by combining polydopamine-modified MXene nanosheets prepared in Example 6 and modified nano-copper prepared in Example 9 in a mass ratio of 2:1. All other conditions remain unchanged.
[0060] Comparative Example 1 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, the product A prepared in Example 1 was replaced by an equal amount of the product D prepared in Comparative Example 1, while all other conditions remained unchanged.
[0061] Comparative Example 2 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, the product A prepared in Example 1 was replaced by an equal amount of product E prepared in Comparative Example 2, while all other conditions remained unchanged.
[0062] Comparative Example 3 Compared with Example 11, Comparative Example 3 did not add nano-additives during the preparation of the bio-stable multifunctional cutting fluid, while all other conditions remained unchanged.
[0063] Comparative Example 4 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, the nano-additives in Comparative Example 4 were all replaced with an equal amount of polydopamine-modified MXene nanosheets, while other conditions remained unchanged.
[0064] Comparative Example 5 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, the nano-additives in Comparative Example 5 were all replaced with an equal amount of modified nano-copper, while other conditions remained unchanged.
[0065] Comparative Example 6 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, Comparative Example 6 replaced polydopamine-modified MXene nanosheets with hexadecyltrimethylammonium bromide-modified MXene in equal amounts, while keeping other conditions unchanged. The preparation process of hexadecyltrimethylammonium bromide-modified MXene was as follows: MXene nanosheets were dissolved in deionized water at a ratio of 1:50 g / ml, hexadecyltrimethylammonium bromide was added, and the mixture was stirred at 70°C for 4 h to obtain hexadecyltrimethylammonium bromide-modified MXene; the mass ratio of hexadecyltrimethylammonium bromide to MXene nanosheets was 1:20.
[0066] Comparative Example 7 Compared with Example 11, in the preparation of the bio-stable multifunctional cutting fluid, Comparative Example 7 replaced the polydopamine-modified MXene nanosheets with unmodified MXene in equal amounts, and the modified nanocopper was replaced with unmodified nanocopper in equal amounts, while other conditions remained unchanged.
[0067] Comparative Example 8 Comparative Example 8 was a semi-synthetic cutting fluid purchased from Shenzhen Meijia Herun Technology Co., Ltd., product number 6030, which claimed to have hard water resistance.
[0068] The cutting fluids of Examples 10-12 and Comparative Examples 1-8 were tested, and the test methods and results are as follows: 500ppm hard water and soft water (hardness ≤ 50ppm) were prepared using Mg2SO4·7H2O and tap water. Hard water stability test: A cutting fluid diluted 8 times with 500ppm hard water was prepared and left at room temperature for 7 days. The state of the diluted fluid was observed. Rust prevention test: A standard HT250 gray cast iron sample (50×25×3mm, surface Ra≤0.8μm) was immersed in the 8-fold diluted cutting fluid prepared with 500ppm hard water. The sample was kept at a constant temperature of 35℃ for 24 hours, then rinsed with water, dehydrated with ethanol, and dried. Lubrication test (average torque test): The Microtap Test system was used to simulate the on-site machining process (using a 7075 aluminum alloy test plate, at room temperature, a rotation speed of 800rpm, a maximum torque of 400Ncm, and a tapping depth of 20mm) to measure the average torque required by the diluted cutting fluid during cutting or deformation in metal processing. The average torque reflects the magnitude of the interaction force between the tool and the workpiece during the cutting process. A lower average torque force means a smoother cutting process and less resistance to the tool, which helps reduce cutting heat and cutting force during the cutting process, thereby reducing the risk of tool wear and workpiece deformation; use soft water to prepare a cutting fluid diluted 8 times for sufficient cooling and lubrication; foaming test: dilute the cutting fluid 8 times with soft water, take 100 mL and put it into a 250 mL graduated cylinder, bubble at an air flow rate of 2 L / min for 5 min; immediately read the initial foam volume (mL); biological stability test: shake culture method, 7-day colony reduction rate (%), prepare 100 mL of cutting fluid diluted 8 times with soft water, inoculate with a mixed bacterial suspension (Pseudomonas aeruginosa and Aspergillus niger); biodegradability test: use the OECD No. test method to test the biodegradability of the diluted cutting fluid.
[0069] Table 1
[0070] Based on Table 1 and from Examples 10-12 and Comparative Examples 1-8, the bio-stable multifunctional cutting fluid prepared in Example 11 of the present invention has good stability, rust prevention, lubrication, biostability and biodegradability. The comparison between Comparative Examples 1-2 and Example 11 shows that a moderate ratio of ethylene oxide and propylene oxide results in good emulsion stability, which can improve the stability, rust prevention, lubrication, and biostability of the cutting fluid. When the PO ratio is too high, the PO chain segments are too long and difficult to degrade, significantly reducing the biodegradability rate. The comparison between Comparative Examples 3-6 and Example 11 shows that the addition of polydopamine-modified MXene nanosheets and modified nano-copper has a synergistic friction-reducing effect, and nano-copper has antibacterial properties, which synergistically enhances the antibacterial effect with the antibacterial agent. Furthermore, cationic hexadecyltrimethylammonium bromide is difficult to degrade and antagonizes the anions in the system. Therefore, adding only a single component or replacing it with hexadecyltrimethylammonium bromide-modified MXene leads to poor results. The comparison between Comparative Example 7 and Example 11 shows that without modification of MXene and nano-copper, the dispersibility is poor, and the aggregation of additives reduces the stability, rust prevention, lubrication, and biostability of the cutting fluid.
[0071] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
[0072] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A biostatic multifunctional cutting fluid, characterized by, The biostable multifunctional cutting fluid comprises the following components by weight: Base oil 20-30%, vegetable oil-ethylene oxide-propylene oxide block copolymer 10-20%, lubricant 5-10%, extreme pressure anti-wear agent 2-5%, rust inhibitor 4-10%, antibacterial agent 0.3-2%, nano additive 0.6-1%, antioxidant 0.1-0.3%, triethanolamine 0.1-0.5%, and the balance is water.
2. The biostable multifunctional cutting fluid according to claim 1, wherein, The preparation method of the vegetable oil-ethylene oxide-propylene oxide block copolymer comprises the following steps: A1: Put vegetable oil and catalyst into a dry and clean high-pressure reaction kettle, heat and vacuumize under stirring to remove trace amount of water in the raw material; A2: Fill nitrogen into the reaction kettle, then add propylene oxide, and increase the temperature for stirring reaction; A3: Add ethylene oxide into the reaction kettle, react, and continue to heat and mature for 1h; A4: Cool the reaction, add acetic acid to neutralize the catalyst, then dissolve the generated salt with water, separate the water phase by standing, obtain the crude product, and further dehydrate under vacuum to obtain the vegetable oil-ethylene oxide-propylene oxide block copolymer.
3. The biostable multifunctional cutting fluid according to claim 2, wherein, In step A1, the vegetable oil comprises at least one of castor oil and guayule oil; the heating temperature is 100-120℃, the vacuum dehydration time is 1-2h; the catalyst is KOH; the amount of the catalyst is 0.1-0.3% of the total mass of the vegetable oil and propylene oxide; in step A2, the stirring reaction conditions are: stirring reaction speed 500-700rpm, stirring reaction temperature 115-130℃, and stirring reaction time 4-6h; the mass ratio of the vegetable oil to propylene oxide is 10:3-10.
4. The biostable multifunctional cutting fluid according to claim 2, wherein, In step A3, the weight ratio of ethylene oxide (EO) to propylene oxide (PO) is 70-80:20-30; the reaction conditions are: reaction temperature 115-130℃, and reaction time 4-6h; in step A4, the mass ratio of acetic acid to KOH is 1.05-1.3:1; and the cooling temperature is 80-90℃.
5. The biostable multifunctional cutting fluid of claim 1, wherein The nano additive is compounded by polydopamine modified MXene nanosheet and modified nano copper at a mass ratio of 2:1; the lubricant is compounded by tetramer castor oil acid ester and M28B tall oil at a mass ratio of 1-1.5:1; the extreme pressure anti-wear agent is a mixture of alkyl phosphate and aryl phosphate at a mass ratio of 1.5-2.5:1; the alkyl phosphate is LB400 phosphate; the aryl phosphate is 468 phosphate; the antibacterial agent is a composite of 1,3,5-tris(2-hydroxyethyl)-1,3,5-hexahydrotriazine and iodoallyl butyl carbamic acid ester at a mass ratio of 1:1; the rust inhibitor is one or more of sunflower diacid, naphthalene diacid, ternary acid, tartaric acid, succinic acid, and isocitric acid; the base oil is rapeseed oil; and the antioxidant is 4,4-methylene(2,6-di-tert-butyl phenol).
6. The biostable multifunctional cutting fluid according to claim 5, wherein, The preparation method of the polydopamine modified MXene nanosheet comprises the following steps: S1: LiF was added to an aqueous HCl solution, and then Ti3AlC2 was slowly added, constant temperature stirring was performed to obtain a multilayer MXene, impurity removal was performed, freeze-drying was performed to obtain MXene sheets; the MXene sheets were added to water and ultrasonic treatment was performed to obtain a 0.3wt% MXene nanosheet aqueous dispersion; S2: Dopamine hydrochloride was dissolved in a Tris-HCl solution and stirring treatment was performed, then the MXene nanosheet aqueous dispersion was added, stirring treatment was continuously performed, washing was performed, and freeze-drying was performed to obtain polydopamine modified MXene nanosheets.
7. The biostable multifunctional cutting fluid according to claim 6, wherein, In the S1, the amount ratio of LiF, HCl, and Ti3AlC2 was 20-40g:300-600mL:20-40g; the concentration of the aqueous HCl solution was 9mol / L; the constant temperature stirring conditions were that the constant temperature stirring temperature was 30-40℃ and the constant temperature stirring time was 20-28h; the impurity removal method was that the multilayer MXene was washed with water until the pH was 7, the precipitate was collected by centrifugation, the precipitate was dispersed again into 150-250mL of water, ultrasonic treatment was performed for 0.5-1.5h at a power of 150-250W, and centrifugation was performed at a speed of 7000-9000rpm for 25-35min; in the S2, the amount ratio of dopamine hydrochloride, the Tris-HCl solution, and the MXene nanosheet aqueous dispersion was 0.6-1.2g:100-200mL:60-140mL; the pH of the Tris-HCl solution was adjusted to 8.5; the stirring treatment time was 25-35min; the mass fraction of the MXene nanosheet aqueous dispersion was 0.3wt%; the continuous stirring treatment time was 20-28h; and the washing method was that the precipitate was washed with ultrapure water and ethanol for 3-5times.
8. The biostable multifunctional cutting fluid of claim 5, wherein, The preparation method of the modified nanometer copper comprises the following steps: P1: A fatty alcohol polyoxyethylene ether was dissolved in tetrahydrofuran, and then potassium hydroxide was added after heating, stirring reaction was performed, cooling was performed in an ice bath, carbon disulfide was added, continuous reaction was performed, and the tetrahydrofuran solvent was removed to obtain potassium fatty alcohol polyoxyethylene ether xanthate; P2: The potassium fatty alcohol polyoxyethylene ether xanthate and copper nitrate were added to water, stirring treatment was performed, sodium borohydride was added for reaction, and centrifugal separation was performed to obtain modified nanometer copper.
9. The biostable multifunctional cutting fluid of claim 8, wherein, In the P1, the amount ratio of the fatty alcohol polyoxyethylene ether, tetrahydrofuran, potassium hydroxide, and carbon disulfide was 10-20g:80-160mL:0.86-1.7g:1.18-2.4g; the heating temperature was 55-65℃; the stirring reaction time was 1.5-2.5h; and the continuous reaction time was 1.5-2.5h; in the P2, the amount ratio of the potassium fatty alcohol polyoxyethylene ether xanthate, copper nitrate, water, and sodium borohydride was 6-12g:2.9-6g:100-200mL:0.45-0.9g; the stirring treatment time was 1.5-2.5h; and the reaction time was 1.5-2.5h.
10. A method for producing the biostatic multifunctional cutting fluid according to any one of claims 1 to 9, characterized by, The preparation method comprises the following steps: Step (1) mix rapeseed oil, 90% of product A, lubricant, extreme pressure anti-wear agent, rust inhibitor, 4, 4-methylene (2, 6-di-tert-butyl phenol) by weight, heat to 50-60℃, then stir at 800-1200 rpm for 20-30 min to form an oil phase; Step (2) dissolve the antibacterial agent in the remaining 10% of product A at 30-40℃, then add 70% of the total water to water at a temperature of 50-55℃ to obtain an aqueous phase, then add the aqueous phase to the oil phase at a temperature of 50-55℃ at a drop rate of 5-10 mL / min, and shear emulsify at a speed of 10,000-15,000 rpm for 25-35 min to obtain an emulsion; Step (3) ultrasonic dispersion of polydopamine modified MXene nanosheet and modified nano-copper with 5% of the total water at a power of 150-250 W for 25-35 min, then add the emulsion under stirring at a speed of 450-550 rpm, and then high shear at a speed of 7000-9000 rpm for 8-12 min, add the remaining 25% of water, adjust the pH to 8.5-9.5 with 1 mol / L triethanolamine, continue stirring for 25-35 min, and then stand at 45-50℃ for 1-2 h to obtain a biostable multifunctional cutting fluid.
Citation Information
Patent Citations
Passivating agent for clayey alkaline heavy metal contaminated soil and preparation method thereof
CN110591721A
Organic-inorganic composite material and preparation method and application thereof in sand stabilization
CN112300806A